Covid Task Force Performance Reviewed from Perceived Stigma and Knowledge about Covid-19 with Infectious Anxiety as Intervening Variables - Sukma Yunita; Mestika Rija Helti; Sumiatik; Ruri Aditya Sari (Science Midwifery, 2022)
Work related to covid-19 creates a feeling of stigma attached to a person or group receiving stigma receiving discriminatory treatment from the majority group, so their environment rejects it. The method of collecting data by distributing questionnaires to 32 covid-19 task force people who were indicated by perceived stigma and anxiety of contracting who were carrying out tasks at 2 big Malls in Medan. The data from the study were processed using validity, reliability tests and linear regression tests to determine their relationship. The covid task force experiences anxiety of contracting, linear regression analysis is carried out to determine its relationship to performance. Based on the results there is a positive relationship between perceived stigma and the performance of the covid-19 task force, with a correlation coefficient value of t = 2.891 with p = 0.0004 (p<0.01). There is no relationship between anxiety and performance, however with a coefficient value of F = 8.763 with p = 0.000 (p<0.01) means perceived stigma and knowledge of the coronavirus with anxiety as an intervening variable together has a significant influence on performance on the covid-19 task force in the era of the Covid-19 pandemic.